Penerapan Kurikulum Merdeka dalam Rencana Pelaksanaan Pembelajaran di Purwakarta - Ali Mursyid; Chyril Futuhana Ahmad; Anggun Kurnia Dewi; Agnes Yusra Tianti (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to find out how the implementation plan for learning in MTsN 2 Purwakarta in an independent curriculum in Arabic subjects. The type of research in this paper is descriptive qualitative. This study shows the application and results of the implementation plan, namely, (1). MTsN 2 Purwakarta is one of the madrasahs appointed by the Ministry of Religion to implement an independent curriculum in accordance with the Decree of the Director General of Pendis Number 3811 of 2022; (2). MTsN 2 Purwakarta is implementing KMA 347 of 2022 concerning Guidelines for the Implementation of the Independent Curriculum in Madrasah as a reference in the implementation of Arabic language learning.